PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL DAN KONSERVATISME AKUNTANSI TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DIBEI PERIODE 2022-2024 - Fadila Putri; Nasirwan (IKRAITH-EKONOMIKA, 2025)
The research problem in this study relates to fluctuations in the financial performance of manufacturing companies, as reflected in changes in Return on Assets during the 2022–2024 period. These fluctuations indicate differences in companies’ abilities to manage assets, capital structure, and accounting policies amid post-pandemic economic conditions. This study aims to analyze the effect of firm size, capital structure, and accounting conservatism on financial performance, with managerial ownership as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period.This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The population of this study consisted of 281 companies, with the sample selected using a purposive sampling method. Based on this technique, a total sample of 40 companies over a three-year period was obtained. The data used in this study are secondary data, collected by downloading financial statements from the official website of the Indonesia Stock Exchange (www.idx.co.id) and the respective company websites. Data analysis was performed using statistical analysis with the assistance of SPSS software. The analytical techniques employed include descriptive statistics, multiple linear regression analysis, and Moderated Regression Analysis.The results of the study show that, first, firm size, capital structure, and accounting conservatism have a significant effect on financial performance. These findings indicate that a company’s financial performance is largely determined by its size, financing policies, and the level of prudence applied in accounting practices.Keywords: firm size, capital structure, accounting conservatism, managerial ownership, financial performance